Cubic NaSbS2 as an ionic-electronic coupled semiconductor for switchable photovoltaic and neuromorphic device applications - Harikesh, Padinhare Cholakkal (2020)
The recent emergence of lead halide perovskites as ionic–electronic coupled semiconductors motivates the investigation of alternative solution‐processable materials with similar modulatable ionic and electronic transport properties. Here, a novel semiconductor—cubic NaSbS2—for ionic–electronic coupled transport is investigated through a combined theoretical and experimental approach. The material exhibits mixed ionic–electronic conductivity in inert atmosphere and superionic conductivity in humid air. It is shown that post deposition electronic reconfigurability in this material enabled by an electric field induces ionic segregation enabling a switchable photovoltaic effect. Utilizing post‐perturbation of the ionic composition of the material via electrical biasing and persistent photoconductivity, multistate memristive synapses with higher‐order weight modulations are realized for neuromorphic computing, opening up novel applications with such ionic–electronic coupled materials.